Age disparities in six-month treatment retention for opioid use disorder. (1st August 2020) - Mintz, Carrie M.; Presnall, Ned J.; Sahrmann, John M.; Borodovsky, Jacob T.; Glaser, Paul E.A.; Bierut, Laura J.; Grucza, Richard A.
Highlights: The relationship between age and OUD treatment retention has been understudied. We examined associations between age and 6-month retention using administrative data. Adolescents with OUD were less likely to be retained at 6 months compared to adults. Age disparities in retention were related to age disparities in medication treatment. Buprenorphine was most strongly associated with 6-month retention for all age groups. Abstract: Background and Aims: Adolescents with opioid use disorder (OUD) are an understudied and vulnerable population. We examined the association between age and six-month treatment retention, and whether any such association was moderated by medication treatment. Methods: In this retrospective cohort study, we used an insurance database with OUD treatment claims from 2006−2016. We examined 261, 356 OUD treatment episodes in three age groups: adolescents (ages 12−17), young adults (18−25) and older adults (26−64). We used logistic regression to estimate prevalence of six-month retention before and after stratification by treatment type (buprenorphine, naltrexone, or psychosocial only). Insurance differences (commercial vs Medicaid) in medication treatment prevalence were also assessed. Results: Adolescents were less likely to be retained compared to adults (17.6 %; 95 % CI 16.5–18.7 % for adolescents; 25.1 %; 95 % CI 24.7–25.4 % for young adults; 33.3 %; 95 % CI 33.0–33.5 % for older adults). This disparity was reduced after adjusting for treatment type. For all ages, buprenorphine was more strongly associated with retention than naltrexone or psychosocial treatment. Adolescents who received buprenorphine were more than four times as likely to be retained in treatment (44.8 %; 95 % CI 40.6–49.0) compared to those who received psychosocial services (9.7 %; 95 % CI 8.8–10.8). Persons with commercial insurance were more likely to receive medication than those with Medicaid (73 % vs 36 %, (χ 2  = 38, 042.6, p  < .001). Conclusions: Age disparities in six-month treatment retention are strongly related to age disparities in medication treatment. Results point to need for improved implementation of medication treatment for persons with OUD, regardless of age or insurance status.